Gambaran Hasil Uji Sterilisasi Alat Kesehatan Steril yang Disimpan dengan Pouch pada Rentang Waktu 0 - 12 Minggu di Unit Sterilisasi Sentral Puskesmas Kecamatan Kebayoran Baru - Iffah, Nabilah Armalia; Wibawanto, Dimas Farhan; Bangun, Dina Evariyana; Arthati, Tresia; Widiany, Astika (Majalah Kedokteran Indonesia, 2024)
Introduction: Reused medical devices are one of the causes of nosocomial infections that occur in health care in Indonesia. Infection occurs when a pathogen spreads to the host such as an invasive procedure or a medical device that enters the body. Differences were found regarding the length of storage time on the level of sterility of medical devices, so it is necessary to determine the length of storage time to prevent nosocomial infections. Objective: To obtain recommendations for the shelf life of sterile medical devices from the results of microbiology test results for devices that stored in pouches.Method: The type of research used is descriptive research. This research was carried out with the aim of identifying the presence or absence of bacteria on instruments that had been sterilized and then stored in pouches at the Central Sterilization Unit of the Puskesmas Kecamatan Kebayoran Baru. Sampling and sample inspection will take place from September 2022 to December 2022. Results: Microbiological examination of Escherichia coli and Bacillus cereus bacteria using a total plate count examination to calculate the number of microbes in the research samples. The results of examinations carried out at 0 days, 1, 4, 7, 10 and 12 weeks on research samples showed that no Escherichia coli and Bacillus cereus bacteria were found.Conclusion: The recommended shelf life for sterile medical devices stored in pouches at the Central Sterilization Unit of the Puskesmas Kecamatan Kebayoran Baru is 12 weeks.